Penerapan Media Kuis Interaktif dalam Meningkatkan Motivasi Pembelajaran Mahasiswa Melalui Aplikasi Kahoot! - Hayati, Ridha Nurul; Alawiyah, Rosidah; Farwati, Wiwik Wida; Elthia, Memy Wardani; Nabila, Fitri; Cahyani, Arie (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2024)
The learning process in higher education often faces challenges such as low student motivation, as observed at Universitas Bumigora. This issue is exacerbated by the use of conventional teaching methods, which are less interactive, making students passive and disengaged. This community engagement project focuses on enhancing student learning motivation by implementing interactive quizzes using the Kahoot! application as part of learning evaluation. A qualitative approach was employed, involving observation, needs analysis, training on Kahoot! usage, and evaluation of its implementation. The mentoring process included workshops and direct application in lectures. The results revealed increased student participation and learning motivation, with students showing greater enthusiasm for their studies. Additionally, this initiative fostered awareness of the importance of integrating technology into academic processes. The transformation supports digital learning innovation and offers an alternative evaluation model to improve the quality of education in higher education settings.